The Anti-psoriatic Effect of Gallic Acid is Associated with the Suppression of Keratin 6 and Nrf2 - Zhang, Jinwei; Qiu, Hong; Cao, Xiaojing; Han, Ling (Letters in Drug Design & Discovery, 2024)
Background: Psoriasis is recognized as an autoimmune dermatosis, and keratin 6 (KRT 6) is a hallmark of psoriasis. Gallic acid (GA) is a natural and small molecule with a series of biological activities. However, the effect of GA on psoriasis has not been clarified. Aims: This study aimed to investigate the anti-psoriatic activity of GA in psoriasis-like mice and in vitro. Methods: The transcriptions of the Homosapiens KRT6 gene, and Musmusculus KRT6 gene, were identified using a quantitative real-time reverse transcriptase PCR (qRT-PCR) assay. Expressions of KRT 6, STAT3, pSTAT3, Nrf2, and pNrf2 in HaCaT cells and skin biopsies were determined with a western blotting assay. The immunofluorescence (IF) assay was used to examine the expression of KRT6, pSTAT3, and pNrf2 in HaCaT cells. The expression of KRT 6, PCNA, Ki67, and CD3 was evaluated on the skin of psoriasis-like mice and quantified with histochemical scores (H scores). Results: GA significantly inhibited KRT 6 gene transcription and expression in psoriasis-like disease both in vitroand in vivo. It significantly inhibited the expression of keratinocyte proliferation markers (PCNA and Ki67), suppressed the expression of CD3 (a marker of T cells), and decreased the thickness of the folded skin, as well as improved the splenomegaly in imiquimod-induced mice similar to psoriasis. Furthermore, the suppressing effect of GA on KRT 6 was abolished by the continuous activation of Nrf2 rather than STAT3, although GA significantly inhibited Nrf2 and STAT3 activation in IL-17A-induced HaCaT cells. Conclusions: KRT 6 acts as a potential target for GA against psoriasis, and the anti-psoriatic effect of GA could be related to Nrf2 signaling.
Keywords: skin biopsies